INSURANCE CONTRACT AS THE BASIS FOR THE SAFETY OF AGRICULTURAL PRODUCERS IN THE REPUBLIC OF SRPSKA - Krstić, Boro; Vasiljević, Zorica; Nedeljković, Miroslav (Economics of Agriculture, 2017)
The aim of the paper is to point out the impact of the insurance contract on the safety of agricultural producers in the Republic of Srpska, based on the assumption that the insurance of crops, fruits and animals is a factor that implies elimination of harmful consequences in case of damage. This attitude of the authors is based on the fact that with the conclusion of an insurance contract in agriculture, the part of the responsibility is transferred to the state (by participation in the co-fnancing of the insurance premium), then to the insurance company (by claiming the damage from the insurance) and fnally to the agricultural producers. Bearing in mind that insurance is very present in all segments of the modern society, which implies a great variety of forms of insurance, the authors of this paper start by presenting a general structure and classifcation of insurance, which also includes the insurance for agricultural purposes. In order to get a realistic picture of the current state of insurance in agriculture in the Republic of Srpska, an analysis of the legal regulation that regulates the mentioned issues was carried out. The authors also conducted a survey among agricultural producers to analyze the reasons why they have a negative interest for this segment of insurance and thus a small number of closed insurance policies with insurance companies. Based on these fndings, this paper gives recommendations for the improvement of the situation and proposals for better solutions which would raise the safety of agricultural producers to a higher level.